Occupational noise exposure and blood pressure among steel industry workers / Wan Nurul Munirah Wan Hamdan, Abdul Mujid Abdullah - Wan Hamdan, Wan Nurul Munirah; Abdullah, Abdul Mujid (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Studies on the relationship between noise exposure at the workplace and hearing impairment among workers have been conducted extensively compared to the effects on non-auditory effects such as blood pressure, stress disorders and sleep disturbance. The purpose of this study was to investigate the effect of occupational noise exposure on workers' blood pressure. A cross-sectional study was conducted among 60 workers from 12 different sections at a steel manufacturing plant. Recruitment of participants was based on inclusive and exclusive criteria as well as voluntary participation. The noise levels exposed to the participants were measured using the Dosimeter for 8 hours working period. Blood pressure was measured using an Automatic Sphygmomanometer before, during, and after working hours. There was a significant relationship between noise exposure and blood pressure; r = 0.51, p < 0.001. There were also significant differences in blood pressure between before, during and after exposure to noise, p <0.05. Exposure to occupational noise can be associated with changes in blood pressure.